Improved performance of a nanorefrigerant-based vapor compression refrigeration system: A new alternative. (February 2021) - Kundan, Lal; Singh, Kuljeet
An attempt has been made to improve the heat transfer characteristics of the vapor compression refrigeration cycle using nanorefrigerant (R134a and Al2 O3, size 20 nm). The performance parameters such as, coefficient of performance, cooling capacity, energy consumption, and temperature drop across condenser and evaporator have been investigated and analyzed. This has been done by varying the mass fraction of nanoparticles of Al2 O3 (0.5–1 wt%) and the flow rate of nanorefrigerant. The investigation has been carried out using three types of nanorefrigerants, i.e. pure R134a, R134a+Al2 O3 (0.5 wt%), and R134a+Al2 O3 (1 wt%) at flow rates of 6.5 L/h and 11 L/h, respectively. The coefficient of performance of the refrigeration system using 0.5% of Al2 O3 (wt%) is found to be improving with volume flow rates of nanorefrigerant, i.e. 7.20% for 6.5 L/h and 16.34% for 11 L/h. The use of nanorefrigerant (R134a+Al2 O3 ) has also resulted in a significant increase in the cooling capacity of the refrigeration system. A substantial drop in the temperature across the condenser (3.0–23.77%), and gain in temperature across the evaporator (4.69–39.30%) is also observed for the refrigeration system under investigation.